Illocutionary Speech Acts in the Poem Ayyuha al-Nas by Tamim al-Barghouti - Yaumal Fikri; Zulkhairi; Rizki Rinaldi (Jurnal Bahasa dan Sastra Pusaka Cendekia, 2025)
This study analyzes the act of illocution speech in the poem "Ayyuha al-Nas" by Tamim al-Barghouti with a pragmatic approach based on Searle's speech theory theory. This poem is an important representation of contemporary Arab socio-political poetry that is loaded with messages of leadership, social criticism, and affirmation of cultural identity. This study uses a descriptive qualitative method with text analysis, covering five categories: directive, expressive, representative, commissive, and declarative. The results of the study show that this poem is dominated by assertive (representative) and expressive illocution, which functions as a moral invitation, collective awareness, and the formation of social identity. This research expands the pragmatic study of Arabic literature and affirms the position of poetry as a medium of public discourse. Penelitian ini menganalisis tindak tutur ilokusi dalam puisi “Ayyuha al-Nas” karya Tamim al-Barghouti dengan pendekatan pragmatic berbasis teori tindak tutur Searle. Puisi ini merupakan representasi penting dari puisi social-politik arab kontemporer yang sarat dengan pesan kepemimpinan, kritik social, dan afirmasi identitas budaya. Penelitian ini menggunakan metode kualitatif deskriptif dengan analisis teks, mencakup lima kategori: direktif, eskpresif, representative, komisif, dan deklaratif. Hasil penelitian menunjukkan bahwa puisi ini didominasi tindak ilokusi Asertif (representatitive) dan ekspresif, yang berfungsi sebagai ajakan moral, penyadaran kolektif, dan pembentukan identitas social. Penelitian ini memperluas kajian pragmatic sastra arab dan menegaskan posisi puisi sebagai medium wacana public.